The Effect of Flash Cards Media on Maharah Kalam Students of MAN 2 Model Medan: Pengaruh Media Flash Cards Terhadap Maharah Kalam Siswa MAN 2 Model Medan - Khairani, Dia Ayu; Nasution, Sahkholid (STUDI ARAB, 2023)
The purpose of this study was to determine the effect of the use of flash cards on the speaking skill of the students of MAN 2 Model Medan. This research method uses quantitative research with experimental research types. The population of this study were students of class XI MAN 2 Medan Model with a total of 391 students, the research sample consisted of two groups, namely the experiment class (a class that was given learning using flash cards media) and the control class (a class that was not given treatment), each class consisted of 36 students. The technique of taking samples using random sampling. Methods of data analysis using validity test, reliability test, normality test, homogeneity test, and hypothesis testing. The results of the t-test analysis obtained t count (25.684) > t table (1.667) with a significance of 0.05, it can be said that H0 is rejected, or it can be concluded that H1 is accepted. Thus, students who are given learning using flash cards media effect increasing their speaking skills in Arabic lessons.